The impact of intellectual capital disclosure on cost of equity capital: A case of French firms - Boujelbene, Mohamed Ali (2013)
The purpose of this paper is to examine empirically the impact of intellectual capital disclosure (IC) on cost of Equity capital. The empirical research is based on companies listed in the French SBF 120 stock market index. The findings confirm our hypotheses that stipulate the existence of a significant and negative association between intellectual capital disclosure with its two components (human capital, structural) and the cost of equity. However, the negative impact of the relational capital disclosure is not validated. The results in this paper are of considerable importance to both policy makers and firms. In fact, the understanding of the impact of Intellectual capital disclosure on cost of equity capital helps policy makers in the evaluation of the costs and benefits of disclosure. Moreover, with regard to managers of firms, the results show the benefit of enhanced IC disclosure regarding the reduction in their cost of capital. This study is one of the very first to provide empirical evidence of the association between Cost of equity capital and the level of disclosure in the three individual intellectual capital categories (human; structural and relational capital).